Media Pembelajaran Matematika Bilingual Berbasis Sparkol Videoscribe - Rahmatika, Dwi Fadila; Ratnasari, Nining (Desimal: Jurnal Matematika, 2018)
This research and development aims to determine the feasibility, attractiveness of student responses, and the effectiveness of the development of videoscribe sparkol-based bilingual learning media. The type of research in this development is (Research and Development). The development model used is the ADDIE model with five research steps; Analysis (Analyze), planning (Design), development (Development), Implementation (Implementation), and Evaluation (Evaluation). Data collection techniques using questionnaire sheets and tests. The instrument used was in the form of a questionnaire to determine the feasibility and attractiveness of students' responses, as well as tests to determine the effectiveness of the products developed. Data analysis techniques used are quantitative descriptive and qualitative descriptive. Obtained the results of the average feasibility test for learning media by media experts, material experts, and linguists with a "very good (SB)". The results of the average attractiveness test on the response of students with the criteria "very good (SB)". It can be concluded that the product development of the generated videocribe sparkol bilingual learning media is feasible, interesting, and effective by providing good results in its implementation.